The SREBP-dependent regulation of cyclin D1 coordinates cell proliferation and lipid synthesis - Aldaalis, Arwa; Bengoechea-Alonso, Maria T.; Ericsson, Johan (Frontiers in Oncology, 2022)
The sterol regulatory-element binding protein (SREBP) family of transcription factors regulate cholesterol, fatty acid and triglyceride synthesis and metabolism. However, they are also targeted by the ubiquitin ligase Fbw7, a major tumor suppressor, suggesting that they could regulate cell growth. Indeed, enhanced lipid synthesis is a hallmark of many human tumors. Thus, the SREBP pathway has recently emerged as a potential target for cancer therapy. We have previously demonstrated that one of these transcription factors, SREBP1, is stabilized and remains associated with target promoters during mitosis, suggesting that the expression of these target genes could be important as cells enter G1 and transcription is restored. Activation of cyclin D-cdk4/6 complexes are critical for the phosphorylation and inactivation of the retinoblastoma protein (Rb) family of transcriptional repressors and progression through the G1 phase of the cell cycle. Importantly, the cyclin D-cdk4/6-Rb regulatory axis is frequently dysregulated in human cancer. In the current manuscript we demonstrate that SREBP1 activates the expression of cyclin D1, a coactivator of cdk4 and cdk6, by binding to an E-box in the cyclin D1 promoter. Consequently, inactivation of SREBP1 in human liver and breast cancer cell lines reduces the expression of cyclin D1 and attenuates Rb phosphorylation. Rb phosphorylation in these cells can be rescued by restoring cyclin D1 expression. On the other hand, expression of active SREBP1 induced the expression of cyclin D1 and increased the phosphorylation of Rb in a manner dependent on cyclin D1 and cdk4/6 activity. Inactivation of SREBP1 resulted in reduced expression of cyclin D1, attenuated phosphorylation of Rb and reduced proliferation. Inactivation of SREBP1 also reduced the insulin-dependent regulation of the cyclin D1 gene. At the same time, SREBP1 is known to play an important role in supporting lipid synthesis in cancer cells. Thus, we propose that the SREBP1-dependent regulation of cyclin D1 coordinates cell proliferation with the enhanced lipid synthesis required to support cell growth.